Evaluation of Dental Luxation Traumas in Turkish Western Mediterranean Population between 1999 and 2017: A Retrospective Study - Oz, Esra; Kırzıoglu, Zuhal (UI Scholars Hub, 2020)
Luxation cases reportedly occur more frequently in men than in women, and the frequency decreases with increasing age. It is important to know the characteristics of luxation injuries to take preventive measures and early treatments. Objective: This study aimed to evaluate luxation trauma cases in the Turkish population in the West Mediterranean region between 1999 and 2017. Methods: An 18-year retrospective analysis of records of patients with luxation traumas was performed. Data regarding age groups, gender, trauma types, etiologic factors, trauma locations, number of affected teeth, trauma types with/without crown fracture, and time elapsed from trauma onset until clinic visit were determined. Acquired data were tabulated as numbers and percentages. Results: A total of 1597 teeth, from 885 patients, exposed to luxation trauma were included. The number of injured teeth per child was 1.8, and single tooth trauma was the most common type. The number of trauma patient was higher in the 0–5 age group, and the number of cases was higher in the primary teeth of the 0–3 age group and in the permanent teeth of the 8–12 age group. The maxillary central incisors were the most commonly affected teeth, and the most common cause was falls. The luxation types most frequently presenting with crown fracture were lateral luxation in the primary teeth (60%) and subluxation in the permanent teeth (33.9%). The proportion of patients with avulsion was the lowest among those visiting the clinic within 2 days of trauma. Conclusion: This study revealed that almost half of the trauma patients have a history of luxation trauma. Educational programs for the community regarding causes and prevention of luxation traumas should be continued.